Evaluation of dental staining using a dentifrice containing chlorhexidine and zinc acetate. A doble blind randomized clinical trial - Rovai, Emanuel silva; de Mello Tera, Tabata; Carvalho de Marco, Andréa; Neves Jardini, Maria Aparecida; Pedrine Santamaria, Mauro; David Kerbauy, Warley (Brazilian Dental Science, 2013)
Chlorhexidine is an antiplaque and anti-gingivitis agent that has a well-known efficacy   in dentistry. It has been incorporated in toothpastes and when associate with mechanical cleaning, it can improve the biofilm control. The zinc acetate associated with antiseptics attempts to minimize the staining caused by these products and to enhance the effect of the chlorhexidine. The aim of this study was to evaluate and compare a dentifrice containing chlorhexidine gluconate associated or not with zinc acetate, as the emergence of extrinsic tooth stain and check if there are still improvements of clinical gingival parameters. For this, 30 volunteers 18-50 years of age, of both sexes, among patients FOSJC / UNESP were enrolled. The volunteers were randomly divided into three groups: CHX+Z, consisting of 10 participants who used a dentifrice with 0.8% chlorhexidine gluconate and zinc acetate 1.16%; CHX group, with 10 participants who used a similar formulation dentifrice but zinc acetate, and the Placebo group also with 10 participants who used a dentifrice formulation similar but without the chlorhexidine and zinc acetate. Patients were assessed at day zero, 15, 30, 45 and 60 days when the indexes of plaque, gingival bleeding and staining were collected. The results showed that by day 60, there was a decrease of both plaque index(PI) and the gingival index(GI) for all groups. Additionally, it was observed that both groups using dentifrice containing chlorhexidine, showed more stain than placebo. The CHX+Z group showed less stain compared to the CHX group, but the difference was not statistically significant. The difference between Placebo and Chlorhexidine Groups was statistically significant (p